Bubbleworms and Rogue Planets: Using Science as a Creative Prompt in STEAM Education - Forget, Bettina (The Canadian Art Teacher / Enseigner les arts au Canada)

(untitled) (Canadian Society for Education through Art / Société canadienne d’éducation par l’art, 2025)
The Imagine Aliens project invited participants to design alien planets, create extraterrestrial life forms, and develop artworks and stories to bring these worlds to life. By using science as a creative prompt, the study demonstrates that a balanced interplay of art and science can make STEM subjects more accessible and create deeper engagement with both disciplines. Conducted in Montreal schools, Imagine Aliens engaged students aged 6 to 13, using a custom website and playing cards to guide research and boost the creative process. This article highlights two findings: how the science-based prompts challenged and expanded upon students’ perceptions of extraterrestrial life, and how the artworks became a site for research, imagination, and scientific curiosity. Imagine Aliens entangles academic disciplines, allowing each to influence the other equally, placing the learner’s focus on research, curiosity, and imagination, unrestrained by disciplinary boundaries.